A Revolution of Love: Thinking through a Dialectic that is Not "One". (9th December 2016) - Roberts, Laura
Abstract : Luce Irigaray argues that the way to overcome the culture of narcissism in the Western tradition is to recognize sexuate difference and to refigure subjectivity as sexuate. This article is an attempt to unpack how Irigaray's philosophical refiguring of love as an intermediary works in this process of reimagining subjectivity as sexuate. If we trace the moments in Irigaray's philosophy where she engages with Hegel's dialectic, and rethinks this dialectical process via the question of sexual difference and a refiguring of love, a clearer reading of her work as groundbreaking and ultimately refiguring our (Western) ontological structures becomes possible. Consequently, if we do not understand Irigaray's radical reformulation of love, we will miss her larger ontological project and fail to properly appreciate her comments on other types of difference—for example, differences of race, tradition, religion. This article argues that as we begin to appreciate the ways in which Irigaray refigures both love and thought as the intermediary, an intermediary that fundamentally disrupts phallocentric binary logic, we can begin to imagine how refiguring the most intimate human experience of love can lead us toward the realization of an ethical political community in which difference in all forms is nourished.